The Effectiveness of Using Drill Method for Mastering Self-Introduction to The Seventh Grade Students at SMPN 33 Barru - Nurhadi, Ismeth; Afifah, Ishmah; Muchlis, Nurmina; Sulkifli (IKIP Siliwangi, 2025)
This study aims to evaluate the effectiveness of the drill method in improving speaking skills among 7th-grade students at SMPN 33 Barru, particularly in the context of self-introduction. The research employed a pretest-posttest design with a pre-experimental approach, involving 22 students. The results showed a significant increase in the students' overall average score, from 60 in the pre-test to 84.7 in the post-test, reflecting substantial improvement in their speaking ability. Improvements were also observed across all assessed aspects: Information (59.5 to 86.3), Grammar (59.3 to 82.2), Pronunciation (58 to 82.2), Fluency (58.8 to 82.2), and Confidence (64.3 to 86.3). These findings suggest that the drill method is effective in enhancing various speaking skills, including accuracy, fluency, and student confidence. Therefore, the drill method can be a beneficial teaching approach to improve English speaking skills, particularly for beginners.